The fate of remnant trees after wind disturbances in boreal and temperate forests - Palm-Hellenurm, Kristiina; Bāders, Endijs; Frelich, Lee E.; Köster, Kajar; Metslaid, Marek; Polyachenko, Olga; Seedre, Meelis; Shorohova, Ekaterina; Stanturf, John A.; Vodde, Floortje; Jõgiste, Kalev (Frontiers in Forests and Global Change, 2024)
Trees that survive disturbances are important biological legacies that facilitate forests' recovery and enhance their structural and species diversity, substantially contributing to the resilience of these ecosystems. The dynamic pattern of legacy syndromes sets the understudied aspects of survivors of wind disturbance into focus. Several factors at tree, stand, and landscape scales alter the susceptibility of the remnant trees, and affect their potential to recover and survive subsequent disturbances. The characteristics of the survivors interact with direct stress and mortality drivers such as changed environmental conditions and pressure by pests and pathogens. Climate change further enhances the post-storm vulnerability of the remaining stand. This literature review analyzes the impact of disturbance parameters (e.g., severity, seasonal timing) and characteristics of the affected forest (e.g., tree species composition, successional stage of a forest stand) on the conditions of survivors through post-windthrow stand development. We attempted to reveal the main agents and processes driving the fate of remnant trees and linked delayed mortality patterns to the main stand-scale wind disturbance regimes in Eurasian and North American boreal and temperate forests: (1) stand-replacing, (2) partially stand-replacing, and (3) fine-scale gap disturbance. We found that after standreplacing wind disturbance, the spatial location of the remaining trees largely determines their onward fate, whereas these survivors are generally more susceptible to subsequent mortality compared to trees that survived less severe events. After partially stand-replacing wind disturbance, the structure of the remnant stand as well as characteristics of the individual remnant trees (e.g., species, age, size) largely determine their survival probability. Following a fine-scale gap disturbance, the trees at the gap edge are more likely to die, compared to the trees situated in the stand interior, but the mortality-causing processes usually operate on a longer time scale. Our findings contribute to the current knowledge on post-windthrow stand development and offer insights into temporal stability of these increasingly important biological legacies.